Karakteristik Neglected Fractures di Rumah Sakit Dompet Dhuafa, Bogor January 2019 - December 2020 : Studi Retrospektif - FUAD IQBAL ELKA PUTRA; Basuki Adam (CV. Jasa Sukses Abadi, 2021)
The neglected/late state is when the patients seek treatment more than 2 days or more than 14 days after the fractures occurred and objectively the callus appears in the X-ray, meanwhile the fracture lines are still exist. Fractures are a common condition in musculoskeletal trauma, according to the Riskesdas (2018) fracture 5.5% of all injury cases in Indonesia. Complications can occur in the form of malunion or non-union fracture, to most severe symptoms such as gangrene or death. This research method was taken from medical records of surgical patients at the Dompet Dhuafa Hospital, Bogor from January 2019 - December 2020. The purpose of this study was to provide an overview of the characteristics of Neglected fractures cases at Dompet Dhuafa Hospital. Then we analyzed using SPSS in the form of descriptions of gender, age, mechanism of injury, characteristics of neglected fracture, health insurance nad complications. The results we obtained of the sex of 9 males (56.2%) and 7 females (43.8%), the mean age was ± 38.7 years with an age range of 9 - 68 years old and the most group is 41-50 years old with 6 cases. Injuries caused by traffic accidents only 3 cases (18.8%) the remaining 13 cases (81.2%) were caused by other mechanisms such as falls or collisioned by blunt objects. The mean time of injury is ± 12.7 weeks with a range of 2-52 weeks. The incidence of neglected radial fractures 7 cases (43.8%) was the highest in our study followed by neglected tibia fibula fractures 4 cases (25%), neglected humerus fracture 2 cases (12.5%), neglected tibia fracture, neglected femur fracture, neglected radius ulna fracture 1 case each (6.3%). Complications that occurred in the form of malunion fractures were 4 cases (25%).